2012
DOI: 10.1155/2012/538452
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Farnesoid X Receptor Activation on Intestinal Permeability in Inflammatory Bowel Disease

Abstract: The most important function of the intestinal mucosa is to form a barrier that separates luminal contents from the intestine. Defects in the intestinal epithelial barrier have been observed in several intestinal disorders such as inflammatory bowel disease (IBD). Recent studies have identified a number of factors that contribute to development of IBD including environmental triggers, genetic factors, immunoregulatory defects and microbial exposure. The current review focuses on the influence of the farnesoid X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 82 publications
1
55
0
Order By: Relevance
“…It was concluded that FXR activation in the ileum is reduced in Crohn's patients, secondary to altered enterohepatic circulation of bile acids. TGR5 and FXR agonists may have therapeutic benefit to Crohn's disease patients (Lian et al, 2011;Pols et al, 2011b;Stojancevic et al, 2012;Stepanov et al, 2013).…”
Section: B Inflammatory Gastrointestinal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that FXR activation in the ileum is reduced in Crohn's patients, secondary to altered enterohepatic circulation of bile acids. TGR5 and FXR agonists may have therapeutic benefit to Crohn's disease patients (Lian et al, 2011;Pols et al, 2011b;Stojancevic et al, 2012;Stepanov et al, 2013).…”
Section: B Inflammatory Gastrointestinal Diseasesmentioning
confidence: 99%
“…The therapeutic potential of bile acids and derivatives for treating hepatic and biliary diseases, NAFLD, and metabolic syndrome has been extensively reviewed Fiorucci and Baldelli, 2009;Zollner and Trauner, 2009;Lian et al, 2011;Pols et al, 2011a,b;Adorini et al, 2012;Hollman et al, 2012;Stojancevic et al, 2012;McMahan et al, 2013;Mudaliar et al, 2013;Stepanov et al, 2013;Duboc et al, 2014) and will be briefly summarized. Bile acid sequestrants have long been used for treating gallstone disease.…”
Section: Fatty Liver Disease Diabetes and Obesitymentioning
confidence: 99%
“…[34,35] FXR activation decreases the production of pro-inflammatory cytokines, such as interleukin (IL) 1-beta, IL-2, IL-6, tumor necrosis factor-alpha and interferon-gamma, thereby reducing inflammation and intestinal permeability. [36] Torres et al [37] showed that FXR expression was inversely correlated with neoplastic progression and the severity of colonic inflammation in UC. FXR expression is also reduced in colonic mucosa from patients with primary sclerosing cholangitis (PSC) and UC-associated neoplasia.…”
Section: Min/+mentioning
confidence: 99%
“…While FXR is a nuclear (hormone) receptor, TGR5 is a G-protein-coupled bile acid receptor at the plasma membrane; both receptors mediate the effects of bile acids in the regulation of glucose and lipid metabolism and inflammation [33,34]. Notably, some TGR5 polymorphisms have recently been associated with the pathogenesis of PSC and ulcerative colitis [35,36], while FXR also appears to be involved in the pathogenesis of IBD [37,38,39,40]. Selective TGR5 and FXR agonists as well as dual TGR5/FXR ligands are now available [34].…”
Section: Novel Bile Acid Receptor Ligands Targeting Fxr and Tgr5mentioning
confidence: 99%